Pharmacokinetics and tissue distribution of LN002, a new compound alternative oxidase inhibitor against Cryptosporidium in rats - Ma, Minglang; Zhang, Yongxiang; Fang, Yanjun; Lu, Yixing; Huang, Huiguo; Zeng, Zhenling; Zeng, Dongping (Frontiers in Pharmacology, 2024)
Cryptosporidiosis is considered a crucial zoonotic disease caused by widely distributing parasitic protozoa called Cryptosporidium spp. Nitazoxanide is the only FDA-approved drug but is only effective with a good immune response of the host. In addressing this unmet medical need, we previously identified a compound, namely LN002, as a potent alternative oxidase inhibitor against cryptosporidiosis. To illustrate the pharmacokinetics, absolute bioavailability, and tissue distribution of LN002 in rats, rapid and sensitive HPLC was developed and validated for the separation and detection of LN002 in plasma, tissue samples, and intestinal contents. In this study, a single dose of oral administration and intravenous injection of LN002 was used to determine the levels of LN002 in plasma, tissue samples, and intestinal contents by UHLC. After intravenous administration of 1 mg/kg LN002, the AUC 0-24 h , T 1/2 , V d , and Cl were 7024.86 h⸱ng/mL, 10.91 h, 1.69 L/kg, and 0.11 L/h/kg, respectively. After oral administration of a single dosage of 100, 200, and 400 mg/kg LN002, the T max , C max , AUC 0-24 h , T 1/2 , F, V d , and